2017
DOI: 10.1002/term.2334
|View full text |Cite
|
Sign up to set email alerts
|

Safety and seizure control in patients with mesial temporal lobe epilepsy treated with regional superselective intra‐arterial injection of autologous bone marrow mononuclear cells

Abstract: Temporal lobe epilepsy (TLE) is a highly prevalent syndrome among people with epilepsy, and is usually refractory to drug treatment. Structural and physiological changes, such as hippocampal sclerosis, are often present in TLE patients. The objective of this study is to evaluate the feasibility and safety of intra-arterial infusion of autologous bone marrow mononuclear cells (BMMC) in adults with medically refractory mesial TLE (MTLE) and unilateral hippocampal sclerosis (HS). We enrolled 20 patients who had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Recent research has suggested that BMMC treatment has host-protective paracrine proprieties, which might account for its observed effects in various diseases (Arnous et al 2012;Guerra et al 2018;Kocher et al 2001). In previous studies, the effects of BMMC treatment on the pilocarpine model of epilepsy were assessed during the acute epileptogenic (Costa-Ferro et al 2010;Leal et al 2014) and chronic periods (Costa-Ferro et al 2012;Venturin et al 2011;Zanirati et al 2015), as well as in clinical investigations (DaCosta et al 2018). Recently, an antiinflammatory effect of BMMC treatment was demonstrated in the unpredictable chronic stressors experimental model (do Prado-Lima et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has suggested that BMMC treatment has host-protective paracrine proprieties, which might account for its observed effects in various diseases (Arnous et al 2012;Guerra et al 2018;Kocher et al 2001). In previous studies, the effects of BMMC treatment on the pilocarpine model of epilepsy were assessed during the acute epileptogenic (Costa-Ferro et al 2010;Leal et al 2014) and chronic periods (Costa-Ferro et al 2012;Venturin et al 2011;Zanirati et al 2015), as well as in clinical investigations (DaCosta et al 2018). Recently, an antiinflammatory effect of BMMC treatment was demonstrated in the unpredictable chronic stressors experimental model (do Prado-Lima et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The most serious side effects were laryngeal stridor and swelling of the tongue [ 56 , 134 ], as well as seizures (however, these patients had already experienced seizures before the stem cell treatment) [ 124 , 135 ]. It is exceptionally interesting that patients who had refractory epilepsy or drug-resistant epilepsy, after being given stem cells as a treatment for cerebral palsy, showed less susceptibility to epileptic seizures than before [ 136 , 137 ]. This interesting lead should prompt researchers and clinicians to further explore the use of stem cell therapy in the treatment of epilepsy.…”
Section: Resultsmentioning
confidence: 99%
“…Cell therapy for epilepsy includes a variety of approaches, including the use of MSCs ( Abdanipour et al, 2011 ; Mohammed et al, 2014 ; Park et al, 2015 ; Hlebokazov et al, 2017 , 2021 ; Fukumura et al, 2018 ; Salem et al, 2018 ; Melin et al, 2019 ; Szczepanik et al, 2020 ; Wang et al, 2021 ), mononuclear cells ( Costa-Ferro et al, 2010 ; Leal et al, 2014 ; DaCosta et al, 2018 ), cells of the nervous system ( Baraban et al, 2009 ; Waldau et al, 2010 ; Cunningham et al, 2014 ; de Gois da Silva et al, 2018 ; Upadhya et al, 2019 ), and encapsulated cells expressing various therapeutic factors ( Kanter-Schlifke et al, 2009 ; Kuramoto et al, 2011 ; Nikitidou et al, 2014 ; Falcicchia et al, 2018 ; Paolone et al, 2019 ), as well as exosomes ( Long et al, 2017 ; Xian et al, 2019 ). Cell therapy is an alternative treatment that can be used to reduce the incidence rate of seizures in epilepsy, including drug-resistant epilepsy, as shown in several clinical studies ( Hlebokazov et al, 2017 , 2021 ; DaCosta et al, 2018 ; Milczarek et al, 2018 ; Szczepanik et al, 2020 ).…”
Section: Cell Therapymentioning
confidence: 99%
“…Phase I/II clinical trials have investigated the safety and efficacy of intra-arterial injection of BMCs in TLE patients. Researchers demonstrated safety, improved memory, a decrease in theta activity, and a decrease in spike density ( DaCosta et al, 2018 ).…”
Section: Cell Therapymentioning
confidence: 99%